Battlestar Galactica. Season 4.0 [videorecording (DVD)] - Olmos, Edward James; McDonnell, Mary; Sackhoff, Katee; Bamber, Jamie, 1973-; Callis, James; Helfer, Tricia; Beckel, Graham, 1949-; Bennett, Matthew, 1954-; Stockwell, Dean, 1938- (Universal Studios Home Entertainment, 2009)
The civil war amongst the Cylons escalates and Galactica's quest for Earth continues.